DIFFERENT STYLISTIC DEVICES USED IN RIDDLES IN UZBEK AND ENGLISH - Nazarova Rano Rahimovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
analyze in details stylistic devices used in English and uzbek riddles , differences and similiarity of English and uzbek riddles. To understand more about the way English and uzbek riddles are created.